Nobleman Jan-Samuel Glogowski as a Representative of the Political Elite of Chernihiv Voivodeship in Exile - Myroslava Vorobei (Українознавство, 2020)
The article represents a review of the nobleman Jan-Samuel Głogowski’s biography in the context of his potential affiliation with the political elite of Chernihiv voivodeship. The relevance of this work is due to the fact that the problem of studying Chernihiv establishment in the period of exile, both at the level of comprehensive research and reconstruction of individual biographies, remains virtually unexplored. The local knightly circle existed relatively shortly from the moment of creating a separate Chernihiv voivodeship till the beginning of Khmelnytsky Uprising (1635–1648). In view of this, this administrative unit’s level of organization and consciousness was inferior to the adjacent noble corporations of Ukrainian voivodeships in Rzeczpospolita. However, during the period of 1648–1668, several families were selected among the locals, whose representatives often won ambassadorial elections and performed various functions delegated by the local sejmik. Those were representatives of Woyna-Oranski, Khazhevski, and Glogowski families. This tendency allows suggesting that the process of consolidating Chernihiv gentry along with separating from its members its own elite continued even in exile. Therefore, this paper is an attempt to investigate whether and how successful were the descendants of famous parliamentarians in consolidating their leadership positions. In this regard, the first part of the article focuses on the methodological aspects of the separation of leaders from the local nobility. Based on the work of such researchers as Edward Opalinski, Yolanta Khoinska-Mika, Janusz Dobrowski, Eugeniusz Janas, and the peculiarities of Chernihiv noble corporation in exile, the criteria for determining the elite are highlighted. A particular emphasis is put on the individual authority of a person and their involvement in the affairs of the local nobility. Instead, the second part of the paper analyzes the extent to which Jan-Samuel suited those criteria. Based on the nobleman’s biography, his connection with Chernihiv brotherhood is considered. In particular, the article examines Glogowski’s career, his family ties, the patrons’ issue, and his interest in local affairs.